2014
DOI: 10.1177/1087054714561860
|View full text |Cite
|
Sign up to set email alerts
|

How Is ADHD Assessed and Documented? Examination of Psychological Reports Submitted to Determine Eligibility for Postsecondary Disability

Abstract: This study raises awareness to the aspects of adequate ADHD evaluation and subsequent documentation that can be improved by psychologists. Recommendations are made regarding valid documentation of ADHD for disability determination purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…Furthermore, only 14% of students had documentation meeting all diagnostic criteria when we expanded our analyses to include data based exclusively on students' self-reports. Our findings are consistent with the results of previous studies that also showed a low percentage of college students with documentation supporting their ADHD diagnoses (Joy et al, 2010;Nelson et al, 2014). Altogether, these results yield converging data that clinicians should provide more thorough evidence supporting their diagnostic decisions and recommendations for treatment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, only 14% of students had documentation meeting all diagnostic criteria when we expanded our analyses to include data based exclusively on students' self-reports. Our findings are consistent with the results of previous studies that also showed a low percentage of college students with documentation supporting their ADHD diagnoses (Joy et al, 2010;Nelson et al, 2014). Altogether, these results yield converging data that clinicians should provide more thorough evidence supporting their diagnostic decisions and recommendations for treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In the second study, researchers reviewed 100 psychological reports submitted by college students seeking academic accommodations (Nelson, Whipple, Lindstrom, & Foels, 2014). In contrast to the previous study, the researchers only included students with an ADHD diagnosis and excluded students with comorbid learning disabilities.…”
Section: Clinician's Adherence To Best Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the DSM-5 and the ADA Title I Regulations require additional information regarding functioning to determine the presence of a disability. Testing agencies are often asked to make accommodation decisions based on documentation verifying a clinical disorder but lacking information verifying the impairment severity necessary for a disability determination (Nelson et al, 2014).…”
Section: The Challenges Of Accommodation Determinationsmentioning
confidence: 99%
“…Although collateral report is essential to the detection of ADHD (Molina & Sibley, 2014), only one set of guidelines requested it. All agencies requested evidence of functional limitations, addressing a frequent omission in the reports of qualified evaluators (Nelson et al, 2014).…”
Section: Guidance For Evaluatorsmentioning
confidence: 99%